Measurement properties of the Gross Motor Function Classification System, Gross Motor Function Classification System‐Expanded & Revised, Manual Ability Classification System, and Communication Function Classification System in cerebral palsy: a systematic review with meta‐analysis - Piscitelli, Daniele; Ferrarello, Francesco; Ugolini, Alessandro; Verola, Sofia; Pellicciari, Leonardo (Developmental medicine and child neurology, 2021)
Aim To systematically review and meta‐analyse the measurement properties of the Gross Motor Function Classification System (GMFCS), Gross Motor Function Classification System‐Expanded & Revised (GMFCS‐E&R), Manual Ability Classification System (MACS), and Communication Function Classification System (CFCS) in children with cerebral palsy (CP). Method Six databases were searched. Articles on the measurement properties of the GMFCS, GMFCS‐E&R, MACS, and CFCS administered to children with CP were included. Quality was assessed by means of the COnsensus‐based Standards for the selection of health Measurement INstruments (COSMIN) Risk of Bias checklist. The level and grading of evidence were defined for each measurement property. Results Forty‐four articles were included in the systematic review and 37 articles were included in the meta‐analysis. The level (grading) of evidence was strong (positive) for reliability and construct validity. Content validity displayed an unknown level of evidence for the GMFCS, limited evidence (positive) for the MACS, and moderate evidence (positive) for the CFCS. There was moderate (positive) evidence for measurement error in the GMFCS and MACS. The level of evidence for responsiveness was unknown. No studies investigated cross‐cultural validity. Interpretation These instruments can be used by health care professionals and caregivers to quantify the constructs needed to measure ability in children with CP. Current high‐quality evidence supports the use of these tools to classify ability in children with CP. Adopting the COSMIN guidelines, content, and cross‐cultural validity should be investigated further. What this paper adds Strong evidence supports the reliability and construct validity of the GMFCS, GMFCS‐E&R, MACS, and CFCS as functional classification systems in children with cerebral palsy. The GMFCS, GMFCS‐E&R, MACS, and CFCS can be used by both health care professionals and caregivers. The GMFCS, GMFCS‐E&R, MACS, and CFCS should not be used to detect change. What this paper adds Strong evidence supports the reliability and construct validity of the GMFCS, GMFCS‐E&R, MACS, and CFCS as functional classification systems in children with cerebral palsy. The GMFCS, GMFCS‐E&R, MACS, and CFCS can be used by both health care professionals and caregivers. The GMFCS, GMFCS‐E&R, MACS, and CFCS should not be used to detect change. This systematic review is commented by Palisano on page 1242 of this issue.